THE EFFECT OF THE PROBIOCORM NUTRITIONAL SUPPLEMENT ON MORPHOLOGICAL INDICATORS OF RABBIT BLOOD (Eureka Journal of Health Sciences & Medical Innovation, 2026)
ProBioKorm is a feed additive created on the basis of local probiotic bacteria and used in animal nutrition. This universal feed supplement improves feed quality, enhances digestion and absorption of nutrients, prevents and treats various bacterial diseases in animals, and increases the productivity of farm animals.
Keywords: ProBioKorm, probiotic, erythrocytes, leukocytes, Hikol, clinical, hemoglobin, tivit.